Penanganan Nyeri Pada Penderita Gout Arthritis dengan Menggunakan Kompres Jahe - mukhlish hidayat; Mei Lestari Ika Widyyati; Atika Jatimi (Indonesian Health Science Journal, 2024)
Gout Arthritis is a disease caused by a number of purine metabolism products in the body. Gout arthritis symptoms usually include pain in the body's joints, inflammation in the joints that are used too often and redness in the area where gout arthritis occurs, stiffness and swelling of the joints that are used too often. Objective: Identify the effect of ginger compresses on pain in sufferers of Gouty Arthritis. Method: The research design used in this research is a pre-experimental study with a one grouppretest and posttest design carried out on one group only without using a control or comparison group. The population in this study were all gouty arthritis patients in the working area of the Kamoning health center, a sample of 30 people and using simple random sampling. The first statistical test used Wilcoxon to determine the effect of ginger compress on pretest and posttest pain. Results: The results of the non-parametric test, namely the Wilcoxon test, obtained a P value of 0.000, meaning that pain management using ginger compresses is very effective. Conclusion: There is an effect of ginger compresses on reducing the pain scale in patients with gouty arthritis before and after ginger compresses